3D bioprinting technologies and bioinks for therapeutic and tissue engineering applications. Issue 4 (12th November 2018) - Choi, Yeong-Jin; Park, Jeong Hun; Jang, Jinah; Cho, Dong-Woo
3D bioprinting has steadily evolved and a variety of relevant research applications are being pursued in conjunction with recent advances in 3D bioprinting. 3D bioprinting facilitates the creation of physiologically relevant geometries and complex structures through precise spatial control of cells and biomaterials. One such development is known as bioink, a type of cell-encapsulation material that recapitulates the extracellular matrix. In this review, we provide an in-depth assessment of the 3D bioprinting technologies and bioinks that have been employed to date in the field of therapeutics and tissue engineering. We further discuss the latest achievements of 3D bioprinting in integumental, musculoskeletal and otolaryngological applications, as well as future perspectives for 3D bioprinting technologies.